Forgiveness Therapy untuk Meningkatkan Self Acceptance dan Happiness pada Korban Orangtua Bercerai - Akta Ririn Aristawati; Ananda Putri; Herlan Pratikto (Faculty of Psychology, Universitas Semarang, 2023)
Abstract: This study aims to determine the effect of forgiveness therapy to increase self-acceptance and happiness in victims of divorced parents. This study used a quantitative experimental method with a pretest-posttest control group design involving 8 early adults with an age range of 20 to 30 years, which were divided into 2 (two) groups, namely 4 people in the experimental group and 4 people in the control group. Data were obtained through 2 scales, namely the self-acceptance scale and the happiness scale which were given before and after treatment in the form of forgiveness therapy. This study used the Mann Whitney test with a value of p=0.021 (p<0.05) for self-acceptance and a value of p=0.020 (p<0.05) for happiness. These results indicate that forgiveness therapy can significantly increase self-acceptance and happiness in victims of divorced parents.Keywords: Forgiveness Therapy, Happiness, Self Acceptance Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh forgiveness therapy untuk meningkatkan self acceptance dan happiness pada korban orang tua bercerai. Penelitian ini menggunakan metode kuantitatif eksperimen dengan desain penelitian pretest-posttest control group design yang melibatkan 8 orang dewasa awal dengan rentang usia 20 hingga 30 tahun, yang terbagi menjadi 2 (dua) kelompok yaitu 4 orang dalam kelompok eksperimen dan 4 orang dalam kelompok kontrol. Data diperoleh melalui 2 skala yaitu skala self acceptance dan skala happiness yang diberikan sebelum dan sesudah perlakuan berupa forgiveness therapy. Penelitian ini menggunakan uji Mann Whitney dengan nilai p=0,021 (p<0,05) untuk self acceptance dan nilai p=0,020 (p<0,05) untuk happiness. Hasil ini menunjukkan bahwa forgiveness therapy dapat meningkatkan self acceptance dan happiness pada korban orang tua bercerai secara signifikan.Kata Kunci: Forgiveness Therapy, Happiness, Self Acceptance